Density, Morphometrics, Length–Weight Relationship, and Condition Factors of Manila Clams (Ruditapes philippinarum) in Waters Batam City - Fety Andriani; Ramses Ramses; Fauziah Syamsi; Ismarti Ismarti (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2026)
Background: The Manila clam Ruditapes philippinarum is an economically important marine bivalve and a key component of coastal ecosystems. Environmental factors such as sedimentation, salinity fluctuations, and human activities may influence its abundance, growth, and physiological condition. This study aimed to assess the abundance, morphometric characteristics, length–weight relationship, and condition factor of R. philippinarum in the waters surrounding Sarang Island, Batam Plot. Methodology: Sampling was conducted at three intertidal stations—Tempayang Island, Piring Island, and Layang Island—using purposive manual collection within 3 plot observation. Shell length, height, and thickness were measured using digital calipers, and total weight was recorded with a digital balance. Growth patterns were analyzed using log–log regression, while condition factors (K and WR) were used to evaluate physiological status. Findings: 87 individuals of R. philippinarum were recorded at Station 1, 118 at Station 2, and 117 at Station 3. The shell length of Ruditapes philippinarum ranged from 15.2 to 42.6 mm across all sampling stations. The length–weight relationship showed a weak correlation (r = 0.145) with a low coefficient of determination (R² = 0.21%) and a negative allometric growth pattern (b = −0.3419). The WR value (121.81) indicated generally good physiological condition. Water quality parameters were generally within tolerance limits; however, stations with higher total dissolved solids and lower water transparency indicated increased turbidity, which was associated with relatively smaller shell sizes of R. philippinarum compared to stations with better water clarity. Overall, variations in abundance and size among stations were influenced by environmental differences, while the R. philippinarum population remained relatively healthy. Contributions: These findings provide baseline ecological information that can support future monitoring and sustainable management strategies for R. philippinarum resources in intertidal coastal ecosystems